PENGARUH LINGKUNGAN KERJA FISIK DAN NON FISIK SERTA STRES KERJA TERHADAP KINERJA KARYAWAN PABRIK SUKA RASA BAKERY - Nanda Aulia Pangestuti (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2020)
ABSTRACT This research to analize the influence of pshysical work environment, non physical and stress on performance on employee performance. This research is explanatory research with quantitative approach methods. The object of this research is the permanent Pabrik Suka Rasa Bakery with 31 people. The method of data collection in this research used a quaestionnaire with a likert measurement scale while for the data analysis technique in this research using multiple regression analysis. Based on the hypothesis testing, the f test is known that joinly (simultaneously) physical environment, non physical and stress significant effect on employee performance. Keywords: pshysical work environment; non physical; stress; performance.